Hedge fund risk assessment - Martin, David (Henry Stewart Talks, 2007)
Environmental scan/allocation strategies, Discerning how alpha is generated, Criteria for hedge fund success, Evaluating returns, Warning signs to monitor, Portfolio considerations
Archived at 2022/04/04